State of food security & nutrition in Bangladesh 2012 - BRAC Institute of Global Health (BIGH) (BRAC Institute of Global Health, BRAC University, 2014)
Food Security and Nutrition Surveillance Project Report; Other Contributors: Suvadra Datta Gupta, Mehedi Hassan, Sabiha Sultana, Jillian L. Waid, Alayne Adams, Erica Khetran, Sheela Sinharoy, Volha Skarin, and Tasnuva Tabassum.